Case-based learning in collaboration across universities to enhance students' understanding of sustainability - Eriksson, Victor; Holma, Anne-Maria; Lind, Frida (CDIO Initiative, 2023)
Focus on sustainability is increasing in engineering and management education, businesses, and the larger society. In order to cope with sustainability challenges, more holistic pedagogies and practices that foster interdisciplinary and transdisciplinary ways of thinking are needed. Thus, this exploratory paper aims to provide insights into developing a master’s-level course module on sustainability in business networks by using active learning through case-based teaching together with collaboration among three Nordic universities (NTNU, Vaasa, and Chalmers). The paper illustrates the multiple facets of designing, implementing, and evaluating three-party collaborative case-based learning based on an active learning approach that enhances students’ learning and performance. We conclude that the students are actively involved and learn better with case-based learning and can further empathize and associate with the case contexts. This can be achieved through engagement in cross-border collaboration, a mix of student backgrounds, flexibility in choosing cases, and clarity in case materials. Additionally, we encourage teachers to use a combination of innovative active learning methods to promote students’ in-depth understanding of complex sustainability-related challenges.
Keywords: Case-based learning; Active learnin; Online learning; Sustainability; University collaboration; University collaboration Standards: 7, 8; fi=Strateginen johtaminen|en=Strategic Management|